Preliminary data about Paraoxonase-1 (PON-1) as a maker for Feline Infectious Peritonitis (FIP) (International Journal of Health, Animal Science and Food Safety, 2018)
Feline infectious peritonitis (FIP) is a fatal disease in which the definitive diagnosis is achieved by immunohistochemistry (IHC) on post-mortem biopsies. The clinical suspicion is aroused by signalment, clinical signs and several laboratory tests, including alpha-1-acid glycoprotein measurement for which the only validated kit is no longer available. Paraoxonase-1 (PON-1) is a serum enzyme with antioxidant activity, considered as a negative acute phase protein in several species. Since inflammation plays a major role in FIP, and due to the high susceptibility of cats to oxidation, it could be of great interest the evaluation of this enzyme as a diagnostic marker for FIP. The aim of this study was to measure paraoxonase-1 in healthy cats and cats with clinical signs consistent with FIP (both wet or dry form), in order to evaluate the utility of this parameter in the diagnosis of FIP. Sixty-two cats were enrolled and divided into three groups: healthy (n=16), confirmed FIP (n=22) and NON FIP with similar clinical signs (n=24). PON-1 was measured on serum, using a paraoxon-based enzymatic method, already validated in cats. Results showed significantly lower PON-1 activity in FIP cats (mean ± SD: 29.1 ± 16.3 U/mL; median: 24.4; IQR: 16.6-38.3), compared with healthy cats (90.1 ± 24.1 U/mL; median: 86.0; IQR: 76.7-105.7; P
Keywords: Paraoxonase-1; Feline Infectious Peritonitis; Diagnostic marker